Efficacy and safety of oral vs vaginal misoprostol for cervical priming before hysteroscopy: A systematic review and meta-analysis. (December 2019) - Abdelhakim, Ahmed M.; Gadallah, Al-Hussein; Abbas, Ahmed M.
Abstract: Background: There is great controversy regarding the most effective route for cervical priming before diagnostic or operative hysteroscopy. Objective: To evaluate the evidence from published randomized clinical trials (RCTs) about the efficacy and safety of oral vs vaginal misoprostol for cervical priming before hysteroscopy. Search strategy: Electronic databases including PubMed, Cochrane Library, Scopus and Web of Science were searched using the relevant keywords. Selection criteria: All RCTs assessing the effect of oral vs vaginal misoprostol before hysteroscopy for cervical priming were considered. One hundred and ten studies were identified, of which eight studies were deemed eligible for this review. Data collection and analysis: The extracted outcomes were: cervical canal width, ease of dilatation, time for cervical dilatation and adverse effects (nausea, vomiting, diarrhoea, bleeding, fever, abdominal pain/uterine cramping and any complications during the procedure). All statistical analyses were completed using RevMan. Main results: Eight RCTs with 768 patients were included in this meta-analysis. Cervical canal width did not differ significantly between the two routes of misoprostol administration [mean difference −0.25 mm, 95% confidence interval (CI) −0.92–0.42; p = 0.47]. However, the vaginal route was significantly superior to the oral route for reducing the time for cervical dilatation (standardized mean difference 0.17, 95% CI 0.02–0.32; p = 0.03). No significant differences in adverse effects were found between the routes, except for diarrhoea which was significantly less prevalent with vaginal administration of misoprostol (risk ratio 2.48, 95% CI 1.17–5.26; p = 0.02). Conclusions: Oral and vaginal administration of misoprostol before hysteroscopy were similar in terms of cervical canal width, ease of dilatation and various adverse effects, except that the vaginal route was associated with faster cervical dilatation and lower prevalence of diarrhoea.